Deconstructive Analysis of Sufistic Thought in Tejo and Kamba’s Tuhan Maha Asik - Nurhasanah; Evan Afri; Zulfan Sahri (International Journal of English and Applied Linguistics (IJEAL), 2022)
The study is mainly aimed at exploring the Sufistic phenomenon presented in Tejo and Kamba’s book Tuhan Maha Asik by applying deconstructive analysis. Besides, this study also finds out the hidden philosophical meaning revealed in the opposite expression in the book as recommended by Derrida. In this context, deconstruction is concerned not with the discovery of ‘truth’ or of distilling correct conclusions, but rather with the process of questioning itself. It is a process characterized by uncertainty and indeterminacy. It is interesting to explore and reveal the internal logic of ideas and meaning. Tejo and Kamba succeeded in using paradox as a weapon to reveal the truth of thinking from two opposite points on the book. Two contrasting ideas are used to produce an in-depth truth. The characteristics or style of deconstruction in works of Sufism are discussed specifically from what is written on book. From the results of the analysis, it can be concluded that many statements in the book Tuhan Maha Asik describe the phenomenon of God. This characterizes that this book presents many events that are Sufistic in nature. The quotations displayed to prove that this understanding must continue to be evaluated in order to create depth and self-awareness of God's existence.